Zoona mobile money: investing for impact (cases A and B). Issue 2 (19th June 2017) - Bazley, John; Rayner, Cynthia Schweer; Power, Aunnie Patton
Abstract : Subject area: Impact investing, Social enterprise. Study level/applicability: MBA, EMBA, Executive Education. Case overview: Zoona mobile money: investing for impact details a slightly altered version of the real events that occurred in late 2011 with the series A round of investment in Zoona, a mobile money business in Zambia. The focus is on the decisions that have to be made by the management team of a socially innovative tech start-up (Zoona) providing mobile money and financial services to previously unbanked consumers in Zambia. Expected learning outcomes: By the end of this case, the student should be able to: understand the basics of term sheets and be able to perform a high level analysis and comparison of two distinct term sheets; identify investor objectives, ultimately recognising the general differences between private equity and venture capital investors; identify and weigh the costs and benefits of term sheets, as well as identify negotiating points and necessary trade-offs in the investment process; and identify and understand the "soft" benefits of investors and weigh these in relation to a term sheet analysis. Supplementary materials: Teaching notes are available for educators only. Please contact your library to gain login details or email support@emeraldinsight.com to request teaching notes. Subject code: CSS 1: Accounting and Finance.